Assessment of the solvency of SMEs: an application of the logistic regression model - BOUAZZARA, Ahlem; BAHA, Riad; BEKTACHE, Fatiha (Dirassat Journal Economic Issue, 2020)
The prediction of the credit risk of SME has been largely addressed by the financial and accounting literature. Many research works have led to models and prediction techniques that can be adapted to different countries and sectors of activity. In this study, we aim to assess the risk of insolvency of SMEs using a logistic regression model on a sample of Algerian SMEs requested from the construction, public works and hydraulic (BTPH) sector.